1994
DOI: 10.1177/0887302x9401200404
|View full text |Cite
|
Sign up to set email alerts
|

Equity, Attribution, and Reactance in Giving and Receiving Gifts of Clothing

Abstract: This study explores equity, attribution, and reactance theories as they relate to giving and receiving gifts of clothing. About 100 each of male and female subjects responded to a set of affective statements written to express the three theories and other aspects of giving and receiving clothing gifts. Factor analyses of responses resulted in four factors for each sex, three of which were similar in content. For each sex, the first factor concerned receiving gifts and incorporated the three theories. The follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 16 publications
3
7
0
Order By: Relevance
“…Also, the females had larger standard deviations for all 18 adjectives across all &brics; thus the females' responses were also more heterogeneous -more polarized-than those of the males. The response pattern in this research paralleled those reported by Home (1991), Manikowske and Winakor (1991), and Winakor, Canton, and Wolins (1980).…”
Section: Hypothesissupporting
confidence: 78%
See 4 more Smart Citations
“…Also, the females had larger standard deviations for all 18 adjectives across all &brics; thus the females' responses were also more heterogeneous -more polarized-than those of the males. The response pattern in this research paralleled those reported by Home (1991), Manikowske and Winakor (1991), and Winakor, Canton, and Wolins (1980).…”
Section: Hypothesissupporting
confidence: 78%
“…The U. S. females' responses were also more heterogeneous than those of the males. The response pattern of U. S. males and females in this research was similar to those reported by Winakor, Canton, and Wolins ( 1980), Manikowske and Winakor ( 1991), and Home (1991). However, the response pattern of native Korean speakers was different from that of native English speakers.…”
Section: Physical Hand Properties Of Fabrics Selected For Final Data supporting
confidence: 77%
See 3 more Smart Citations